2022
DOI: 10.3389/fpls.2022.1005261
|View full text |Cite
|
Sign up to set email alerts
|

Multigene manipulation of photosynthetic carbon metabolism enhances the photosynthetic capacity and biomass yield of cucumber under low-CO2 environment

Abstract: Solar greenhouses are important in the vegetable production and widely used for the counter-season production in the world. However, the CO2 consumed by crops for photosynthesis after sunrise is not supplemented and becomes chronically deficient due to the airtight structure of solar greenhouses. Vegetable crops cannot effectively utilize light resources under low-CO2 environment, and this incapability results in reduced photosynthetic efficiency and crop yield. We used cucumber as a model plant and generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Fructose-1,6-bisphosphatase is present in soybean chloroplasts, and its reductive activation process also affects chloroplast photosynthesis [46,47]. Studies have shown that the joint involvement of multiple genes for photosynthetic carbon assimilation positively affects photosynthesis and biomass yield [48,49]. In this study, ribulose-5-phosphate isomerase (SoyZH13_03G225100) and fructose-1,6-bisphosphatase (SoyZH13_16G150600) were detected to be differentially expressed in the mid-canopy leaves at T1-T3 of LD32, but no expression of the above differential genes was detected in SND28.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fructose-1,6-bisphosphatase is present in soybean chloroplasts, and its reductive activation process also affects chloroplast photosynthesis [46,47]. Studies have shown that the joint involvement of multiple genes for photosynthetic carbon assimilation positively affects photosynthesis and biomass yield [48,49]. In this study, ribulose-5-phosphate isomerase (SoyZH13_03G225100) and fructose-1,6-bisphosphatase (SoyZH13_16G150600) were detected to be differentially expressed in the mid-canopy leaves at T1-T3 of LD32, but no expression of the above differential genes was detected in SND28.…”
Section: Discussionmentioning
confidence: 99%
“…Fructose-1,6-bisphosphatase is present in soybean chloroplasts, and its reductive activation process also affects chloroplast photosynthesis [46,47]. Studies have shown that the joint involvement of multiple genes for photosynthetic carbon assimilation positively affects photosynthesis and biomass yield [48,49].…”
Section: Discussionmentioning
confidence: 99%
“…PCC 7942 ictB in soybean soybean Transgenic plants exhibited higher photosynthesis, growth, and drought resilience compared to wild type plants in greenhouse, field, and drought mimic conditions [ 87 ] Incorporation of BicA and SbtA proteins into the chloroplast of Arabidopsis Arabidopsis The installation of authentic BicA and SbtA to the chloroplast inner envelope membrane has been achieved via the proteolytic cleavage of chimeric proteins [ 94 ] Overexpression of CsβCA1, CsβCA4, CsSBP and CsFBA cucumber The net photosynthesis biomass yield and photosynthetic rate increased by a maximum of 49 % and 79 % compared to those of the wild type. [ 95 ] Introducing carboxysomes from cyanobacteria into the chloroplasts of CCM-free tobacco tobacco This minimal gene set generates carboxysomes and facilitates autotrophic growth under elevated CO 2 conditions [ 96 ] Introducing partial carboxysomes from cyanobacteria into the chloroplasts of tobacoo tobacco The minimal gene set produces carboxysomes supported the autotrophic growth of transgenic lines at 2 % CO 2 . [ 97 ] Introducing complete carboxysomes from cyanobacteria into the chloroplasts of tobacoo tobacco Constructed complete carboxysomes in tobacco chloroplasts that resemble the native carboxysomes, supporting autotrophic growth in 1 % CO 2 .…”
Section: Direct or Indirect Engineering Rubisco In Plantsmentioning
confidence: 99%
“…In higher plant photosynthetic carbon metabolism, CA accelerates the diffusion of CO 2 to the active site of Rubisco, thereby enhancing the rate of CO 2 fixation. As the only CA that responds to low levels of CO 2 , the significance of βCA in enhancing plant photosynthesis has been substantiated through the overexpression of β-carbonic anhydrase 1 (CsβCA1), β-carbonic anhydrase 4 (CsβCA4) in cucumber [ 95 ]. Introducing carboxysomes from cyanobacteria into the chloroplasts of CCM-free crops is predicted to improve yields by up to 60 % under hot and dry conditions [ 88 ].…”
Section: Direct or Indirect Engineering Rubisco In Plantsmentioning
confidence: 99%